Idiomatic Meaning in English Compounds: A Semantic Analysis of Non-Literal Interpretations - Luwiti, Sri Rumiyatiningsih (Pascasarjana, Universitas Negeri Gorontalo, 2024)
Idiomatic compounds in English often present challenges for learners, particularly those for whom English is a second language (ESL). These compounds, such as